The Implementation of Inpatient Identification In Hospital X Yogyakarta - Totok Sundoro (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2020)
ABSTRACTBackground: Hospitals must be able to provide a guarantee of security and protection against the service impact that have fulfilled the quality standards to meet the community's right on the quality services. Hospital patient safety is a system where hospitals make patient care safer. Safety in service can be started from the accuracy of patient identification. The observational results show a mismatch in its implementation.Objectives: The purpose of this study is to determine the discrepancy in the implementation of inpatient identification on regulations, implementation, and obstacles in the implementation of inpatient identification in hospitals.Methodology: This research is a case study with a qualitative approach producing descriptive data. Research subjects consisted of Management, Staff, and Patients with purposive sampling techniques. The instruments used in this qualitative study were guidelines for tracking observation, in-depth interviews, and FGDs. Data analysis uses reduction, presentation, and drawing conclusions.Results: The implementation of inpatient identification in the hospital has been applied well. Based on the results of regulatory search, interviews, documentation, observations and simulations, it is obtained that the score achievement is with a value of 55 (91.67%) which means completed.Discussions: The implementation of inpatient identification in supporting patient safety programs can run well if there is an effort to build a patient safety culture in the hospital through support from the leadership, supervision and supervision, training and socialization, motivating staff and conducting monitoring and evaluation.Conclusion: Overall the implementation of inpatient identification at the hospital has been run well. There are policies that regulate, but the implementation of non-compliance is due to non-compliance staffs. There are some contents of the medical record sheet and the filling is not in accordance with standards and there is a limitation of identity label.